Do metaphors make opinions?: An empirical study on the effect of metaphorical framing on the opinion on surrogacy - Mohnke, Margaux; Christmann, Ursula; Roos, Yannick; Thomale, Chris (Metaphor and the social world, 2022)
Introduction: A frame makes specific information about a topic more salient. Metaphors can be used as frames to influence people’s opinions on controversial political topics as well as on health-related topics. This study aims to determine the influence of metaphorical frames on the opinion towards surrogacy and examines whether specific aspects of surrogacy are more prone to the influence than others. Method: 236 participants were assigned to one of three groups with different metaphorical frames for surrogacy and thereafter completed the Attitude Towards Surrogacy Questionnaire. To investigate if participants’ opinions on surrogacy were influenced by the frame used for surrogacy, three ANOVAS were conducted. Result: The main effect of the ANOVAS revealed that opinion towards payment of the surrogate mothers, but not the attitude towards surrogacy in general, was influenced by the metaphorical frame used for surrogacy. Discussion: The results support the idea that a metaphorical frame can evoke reactance regarding the payment of surrogate mothers. Participants might resist the frame of the metaphorical term for surrogacy as an unemotional business act, by favouring less monetary compensation of the surrogate mother, when the metaphorical frame implies that surrogates only help intended parents for the monetary compensation.
Epub ahead of print
Gesehen am 09.02.2022